Scavenger receptor BI, not LDL receptor, mediates adrenal stress response - Ito, Misa (Arterioscler Thromb Vasc Biol, 2020)
OBJECTIVE: Adrenal gland secretes stress-induced glucocorticoids (iGC) in order to coping with stress. Previous study showed that scavenger receptor BI null (SR-BI−/−) mice failed to generate iGC in stress conditions, suggesting that SR-BI-mediated cholesterol uptake from HDL is a key regulator for iGC production. However, the LDL/LDL receptor (LDL/LDLr) pathway can also provide cholesterol for iGC synthesis, but rodents have limited LDL levels in circulation. Here, we generated SR-BI−/−ApoBtg mice with normal LDL levels in circulation to determine the relative contribution of the HDL/SR-BI and LDL/LDLr pathways to iGC production in stress conditions. APPROACH AND RESULTS: To obtain mouse models with normal LDL levels, SR-BI−/− mice were bred to ApoBtg mice. Then, the F1 SR-BI+/−ApoBtg mice were backcrossed to SR-BI−/− to obtain SR-BI−/−ApoBtg, SR-BI−/−ApoBwt and SR-BI+/+ApoBtg mice. We first examined the lipoprotein profile, which shows a 6.5-fold increase in LDL levels in SR-BI−/−ApoBtg mice compared to SR-BI−/−ApoBwt mice. Then, we induced stress with adrenocorticotropic hormone (ACTH) and cecal ligation and puncture (CLP). One hour after ACTH stimulation, SR-BI+/+ApoBtg control mice produced iGC (14.9 folds), but both SR-BI−/−ApoBwt and SR-BI−/−ApoBtg showed no iGC production (p < 0.001). Three hours after CLP treatment, SR-BI+/+ApoBtg control mice showed iGC production (6.4 folds), but both SR-BI−/−ApoBwt and SR-BI−/−ApoBtg mice showed no iGC production (p < 0.001). CONCLUSIONS: SR-BI−/−ApoBtg mice fail to produce iGC in stress conditions even though with restored LDL levels in circulation. These findings clarify that the HDL/SR-BI, not LDL/LDLr, pathway is responsible for iGC production in stress conditions.